Beyond the Hippocampus and the SVZ: Adult Neurogenesis Throughout the Brain - Jurkowski, Michal P.; Bettio, Luis; K. Woo, Emma; Patten, Anna; Yau, Suk-Yu; Gil-Mohapel, Joana (Frontiers in Cellular Neuroscience, 2020)
Convincing evidence has repeatedly shown that new neurons are produced in the mammalian brain into adulthood. Adult neurogenesis has been best described in the hippocampus and the subventricular zone (SVZ), in which a series of distinct stages of neuronal development have been well characterized. However, more recently, new neurons have also been found in other brain regions of the adult mammalian brain, including the hypothalamus, striatum, substantia nigra, cortex and amygdala. While some studies have suggested that these new neurons originate from endogenous stem cell pools located within these brain regions, others have shown the migration of neurons from the SVZ to these regions. Of note, it has been shown that the generation of new neurons in these brain regions is impacted by neurologic processes such as stroke/ischemia and neurodegenerative disorders. Further, numerous factors such as neurotrophic support, pharmacologic interventions, environmental exposures and stem cell therapy can modulate this endogenous process. While the presence and significance of adult neurogenesis in the human brain (and particularly outside of the classical neurogenic regions) is still an area of debate, this intrinsic neurogenic potential and its possible regulation through therapeutic measures present an exciting alternative for the treatment of several neurologic conditions. This review summarizes evidence in support of the classic and novel neurogenic zones present within the mammalian brain and discusses the functional significance of these new neurons, as well as factors that regulate their production. Finally, it also discusses the potential clinical applications of promoting neurogenesis outside of the classical neurogenic niches, particularly in the hypothalamus, cortex, striatum, substantia nigra, and amygdala.